In silico models for cellular and molecular immunology: successes, promises and challenges. - Chakraborty, A; Dustin, M; Shaw, A (2003)
Although most immunologists do not routinely combine experiments with theoretical and mathematical modeling, new insights can be gained from this interdisciplinary approach. But what makes a good theoretical model?